2016
DOI: 10.1039/c6sc00589f
|View full text |Cite
|
Sign up to set email alerts
|

A supramolecularly tunable chiral diphosphine ligand: application to Rh and Ir-catalyzed enantioselective hydrogenation

Abstract: A supramolecularly tunable chiral bisphosphine ligand bearing two pyridyl-containing crown ethers was synthesized and applied in Rh or Ir-catalyzed asymmetric hydrogenations in high yields with excellent ee values (90–99% ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 75 publications
2
7
0
Order By: Relevance
“…Similar to the case for many other cationic [Ir­(C ∧ N) 2 (P ∧ P)] + iridium complexes found in the literature, the absorption spectra of complexes 1 – 9 are dominated by multiple bands originating from ligand-centered π–π* transitions and MLCT transitions. The intense bands at higher energies (240–320 nm) are assigned to the spin-allowed ligand-centered (LC) 1 π–π* transitions.…”
Section: Resultssupporting
confidence: 77%
“…Similar to the case for many other cationic [Ir­(C ∧ N) 2 (P ∧ P)] + iridium complexes found in the literature, the absorption spectra of complexes 1 – 9 are dominated by multiple bands originating from ligand-centered π–π* transitions and MLCT transitions. The intense bands at higher energies (240–320 nm) are assigned to the spin-allowed ligand-centered (LC) 1 π–π* transitions.…”
Section: Resultssupporting
confidence: 77%
“…The effect of anion BAr F ‐ was also investigated by using ( n ‐Bu) 4 NBAr F as a control additive since ( n ‐Bu) 4 N + is a quaternary ammonium ion which could hardly be complexed by crown ethers on the ligand (Figure S3). It was shown that the existence of BAr F − deactivated the reaction, which is similar to our previous research [10] . In cyclohexane, the addition of ( n ‐Bu) 4 NBAr F provided only <5 % conversion (entry 10).…”
Section: Resultssupporting
confidence: 88%
“…The ligands (−) and (+)‐ 1 (Figure 1) were prepared according to our previous work [10] . The 1‐phenylethanammonium salts ( rac )‐, ( R )‐, and ( S )‐ 2 a and 1‐(naphthalen‐2‐yl)ethanammonium salts ( rac )‐, ( R )‐, and ( S )‐ 2 b with the BAr F ‐ (tetrakis[3,5‐bis(trifluoromethyl)phenyl]borate) anion (Scheme 1) were chosen as guests to complex with the pyridyl‐containing crown ethers on Xyl‐P16C6‐Phos to investigate whether the configuration of guests can influence the catalytic activity and enantioselectivity of the ligand in asymmetric hydrogenation reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chiral tetrahydroquinoline motifs have been found in various biologically active compounds, pharmaceuticals, and natural products. Accordingly, the development of efficient synthetic protocols for optically active tetrahydroquinolines has garnered considerable research interest. Owing to the utility of consecutive one-pot protocols, there are several examples of the one-pot synthesis of optically active tetrahydroquinolines, wherein the construction of the quinoline scaffolds and the asymmetric reduction of the resulting quinolines are performed in tandem . However, these one-pot protocols rely on the combination of two different catalyst systems: one for the preparation of the parent quinoline scaffolds and the other for enantioselective reduction of the resulting quinolines into tetrahydroquinolines.…”
Section: Resultsmentioning
confidence: 99%